Innovative Use of Spinner Media as an Interactive Tool in Teaching Fiqh - Lail, Lailatul solicha; Ishari, Nurhafid (Kartika: Jurnal Studi Keislaman, 2025)
This study investigates the application of spinner-based learning media in fiqh instruction within Islamic education. The initiative arises from the need for innovative media that can increase student engagement and improve comprehension of materials often perceived as difficult. Spinner media, with its interactive and adaptable design, is considered a tool capable of attracting attention and fostering active learning. A qualitative case study approach was employed, utilizing observations, interviews, and documentation as data collection techniques. The data were analyzed through stages of reduction, presentation, and conclusion drawing to ensure validity and reliability. The findings reveal that the integration of spinner-based learning media significantly enhanced student participation, enthusiasm, and learning outcomes. Prior to its implementation, fiqh lessons were characterized by monotonous activities and low levels of concentration. However, the use of spinner media transformed the learning atmosphere into a more engaging and effective process, minimizing challenges while maximizing student involvement. These results suggest that spinner-based media serves not only as an instructional aid but also as a motivational tool that supports meaningful and enjoyable learning in Islamic education.